Literature Review: Resilience Factors In Service Sector Employees In The Covid-19 Pandemic - Brahmantya, Daniel Ido; Noviekayati, IGAA (International Conference on Sustainable Health Promotion, 2021)
The Covid-19 pandemic has become a global pandemic that makes all people feel great fear because of its rapid spread. This virus has a variety of effects on mental health, physical health, finances, and how people act on a daily basis. Work from home (WFH) activities started to be introduced across the organization, including employees in the service sector. As a result, employees must quickly adjust to potentially dangerous and unclear conditions. The right variable in this case is resilience. The goal of this literature review is to see what factors influence employee resilience in the service industry. A literature study was conducted based on the topic, technique, and research journal similarities. Eight of the ten papers chosen utilized quantitative methods, one used mixed methods, and one used experimental methods. Employees who worked as nurses, doctors, health care workers, teachers, and frontline workers made up the study's population. The study was carried out in a number of nations, including Indonesia, Turkey, Thailand, Sweden, and the United Kingdom. Sleep quality, positive emotions, life satisfaction, age, employee tenure, work experience, and individual character are all characteristics that promote resilience, according to the findings of eleven studies. If an employee cannot be a resilient person, it will be easy to experience stress and the employee's performance will decrease. If an employee can develop resilience, they will work more calmly, have higher subjective well-being, and be able to deal with potentially dangerous situations.